Development of reinforced composite sandwich panels based on 3D fabrics - Fangueiro, Raúl (2010)
relative new type of sandwich material was investigated, based on 3D knitted sandwich fabric preforms. Due to the integrally interlacement of both sandwich-fabric the skins by the connection yarns – core debonding resistance of panels and structures based on the perform is very high. [1]. In this work the mechanical performance of sandwich composite panels based on sandwich knitted fabrics is presented and discussed. Different 3D sandwich knitted fabric performs have been produced varying the thickness and the interlacement pattern. Composite panels using these performs have been produced using vacuum infusion technique. Panel thicknesses of 8, 15 and 25 mm, using two resin types – polyester and epoxy – have been produced. Materials thus obtained have been tested in tensile, bending and impact. The results obtained are presented, discussed and compared to models. Various samples of 3D sandwich spacer fabrics using vacuum infusion process have been produced in order to study the impregnation process. The dimensional properties investigated for non-impregnated core structures include cross-threads density, areal mass, yarns linear density, etc. Results obtained show that the mechanical performances vary according to the type of 3D knitted sandwich perform and the type of resin used.